ASSIM COMO AS BORBOLETAS: BIANCA E A SÍNDROME DE TURNER - Araujo, Michell Pedruzzi Mendes (2020)
This thesis aims to understand Bianca s life story, a young woman with Turner syndrome. To achieve this goal, we used the methodology of life story built from the memories of young Bianca herself, and from her parents, her siblings and two professionals f